Predicting risk of atrial fibrillation after heart valve surgery: evaluation of a Brazilian risk score - Sá,Michel Pompeu Barros de Oliveira (2012)
OBJECTIVE: The aim of this study is to evaluate the applicability of a Brazilian score for predicting atrial fibrillation (AF) in patients undergoing heart valve surgery in the Division of Cardiovascular Surgery of Pronto Socorro Cardiológico de Pernambuco - PROCAPE (Recife, PE, Brazil). METHODS: Retrospective study involving 491 consecutive patients operated between May/2007 and December/2010. The registers contained all the information used to calculate the score. The outcome of interest was AF. We calculated association of model factors with AF (univariate analysis and multivariate logistic regression analysis), and association of risk score classes with AF. RESULTS: The incidence of AF was 31.2%. In multivariate analysis, the four variables of the score were predictors of postoperative AF: age >70 years (OR 6.82; 95%CI 3.34-14.10; P<0.001), mitral valve disease (OR 3.18; 95%CI 1.83-5.20; P<0.001), no use of beta-blocker or discontinuation of its use in the postoperative period (OR 1.63; 95%CI 1.05-2.51; P=0.028), total fluid balance > 1500 ml at first 24 hours (OR 1.92; 95%CI 1.28-2.88; P=0.002). We observed that the higher the risk class of the patient (low, medium, high, very high), the greater is the incidence of postoperative AF (4.2%; 18.1%; 30.8%; 49.2%), showing that the model seems to be a good predictor of risk of postoperative AF, in a statistically significant association (P<0.001). CONCLUSIONS: The Brazilian score proved to be a simple and objective index, revealing a satisfactory predictor of development of postoperative AF in patients undergoing heart valve surgery at our institution.